Responses of Aquatic Nontarget Organisms in Experiments Simulating a Scenario of Contamination by Imidacloprid in a Freshwater Environment - Queiroz, Lucas Gonçalves; do Prado, Caio César Achiles; de Almeida, Éryka Costa; Dörr, Felipe Augusto; Pinto, Ernani; da Silva, Flávio Teixeira; de Paiva, Teresa Cristina Brazil (Archives of environmental contamination and toxicology, 2021)
Several studies have indicated the presence of the neonicotinoid insecticide imidacloprid (IMI) in aquatic ecosystems in concentrations up to 320.0 µg L −1 . In the present study, we evaluated the effects of the highest IMI concentration detected in surface water (320.0 µg L −1 ) on the survival of Chironomus sancticaroli , Daphnia similis, and Danio rerio in three different scenarios of water contamination. The enzymatic activities of glutathione S-transferase (GST), catalase (CAT), and ascorbate peroxidase (APX) in D. rerio also were determined. For this evaluation, we have simulated a lotic environment using an indoor system of artificial channels developed for the present study. In this system, three scenarios of contamination by IMI (320.0 µg L −1 ) were reproduced: one using reconstituted water (RW) and the other two using water samples collected in unpolluted (UW) and polluted (DW) areas of a river. The results indicated that the tested concentration was not able to cause mortality in D. similis and D. rerio in any proposed treatment (RW, UW, and DW). However, C. sancticaroli showed 100% of mortality in the presence of IMI in the three proposed treatments, demonstrating its potential to impact the community of aquatic nontarget insects negatively. Low IMI concentrations did not offer risks to D. rerio survival. However, we observed alterations in GST, CAT, and APX activities in treatments that used IMI and water with no evidence of pollution (i.e., RW and UW). These last results demonstrated that fish are more susceptible to the effects of IMI in unpolluted environments.